Novel lithium battery negative electrode material as well as preparation method and application thereof
By using silver nanoparticles covering nanolayers in lithium metal negative electrode materials, the problem of uneven lithium deposition leading to lithium dendrites is solved, and the growth of lithium dendrites is suppressed under high current density and the service life of the battery is improved. Effect.
Patent Information
- Application Number
- CN202510031009.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium metal negative electrode materials have uneven lithium deposition when the current density is greater than the limit current density, resulting in the growth of lithium dendrites and reducing the service life of the battery.
Silver nanoparticles coated with nanolayers are used as the negative electrode material. The nanolayer consists of 3,4,5-trihydroxybenzoic acid and polyethyleneimine. Silver nanoparticles coated with polar functional groups are obtained by sonication and centrifugation. .
Suppress the growth of lithium dendrites under high current density, improve the service life of the battery, and maintain the stability of the voltage.
Smart Images

Figure CN119447272A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery materials, and in particular to a novel lithium battery negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium metal has an ultra-high theoretical specific capacity (3860mAh / g) and is considered to be a potential next-generation negative electrode material that can replace graphite. However, lithium metal is prone to produce lithium dendrites during the charging and discharging process, which reduces the battery life and even causes internal short circuits and safety accidents.
[0003] Usually, lithium metal is doped with lithium-philic materials such as silver and magnesium to induce the electrochemical precipitation of lithium ions and inhibit the growth of lithium dendrites. However, this can only be achieved when the current density is less than the limiting current density. When the current density is less than the limiting current density, the lithium ion concentration on the surface of the lithium-philic material is evenly distributed. When lithium ions obtain electrons on the surface of the lithium-philic material and become lithium, lithium can be bound by the lattice of the lithium-philic material and combined with the lithium-philic material. Because the lithium-philic material has a strong affinity for lithium, lithium can nucleate and grow evenly on the surface of the lithium-philic material.
[0004] However, when the current density is greater than the limiting current density, the concentration of lithium ions on the surface of the lithium-philic material is uneven. The lithium nucleation grows quickly where the lithium ion concentration is high, and the lithium nucleation grows slowly where the lithium ion concentration is low, thus forming an uneven plane on the surface of the lithium-philic material and forming lithium dendrites again. Summary of the invention
[0005] The technical problem to be solved by the present invention is that the uneven lithium deposition at the existing lithium metal negative electrode leads to the growth of lithium dendrites when the current density is greater than the limiting current density. The purpose is to provide a new type of lithium battery negative electrode material and its preparation method and application, which can optimize the properties of the surface of the lithium-philic material and inhibit the growth of lithium dendrites caused by the uneven lithium ion concentration caused by the current density being greater than the limiting current density.
[0006] The present invention is achieved through the following technical solutions: The first object of the present invention is to provide a novel negative electrode material for a lithium battery, comprising lithium-philic nanoparticles and a coating nanolayer coated on the outer surface of the lithium-philic nanoparticles, wherein the coating nanolayer contains polar functional groups.
[0007] As a further technical solution of the present invention, the lithium-philic particles are silver nanoparticles, and the coated nanolayer is a polymer of 3,4,5-trihydroxybenzoic acid and polyethyleneimine.
[0008] As a further technical solution of the present invention, the thickness of the coated nanolayer is 0.001-0.5 μm.
[0009] As a further technical solution of the present invention, the mass ratio of the polymer of 3,4,5-trihydroxybenzoic acid and polyethyleneimine is 10:1 or 1:10.
[0010] The second object of the present invention is to provide a method for preparing a novel negative electrode material for a lithium battery, comprising the following steps: S1, adding silver nanoparticles into deionized water to obtain a silver nanoparticle dispersion; S2, dissolving 3,4,5-trihydroxybenzoic acid in a tris(hydroxymethyl)aminomethane buffer solution to prepare a tris(hydroxymethyl)aminomethane solution containing 3,4,5-trihydroxybenzoic acid; dissolving polyethyleneimine in another tris(hydroxymethylaminomethane) buffer solution to prepare a tris(hydroxymethylaminomethane) solution containing polyethyleneimine; S3, under room temperature, adding the two solutions obtained in step S2 to the dispersion in step S1, and letting it stand for a period of time to obtain a dispersion of silver nanoparticles coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine nanolayers; S4, centrifuging the dispersion obtained in step 3, separating the precipitate, drying and collecting the nanoparticles, and finally obtaining the desired negative electrode material.
[0011] As a further technical solution of the present invention, the treatment process of step S1 is: treating at 100W ultrasonic power for 10 minutes, and the silver nanoparticles are evenly dispersed to form a dispersion.
[0012] As a further technical solution of the present invention, the standing time in step S3 is 0.5-30 min.
[0013] As a further technical solution of the present invention, the negative electrode material finally obtained in step S4 is silver nanoparticles coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine containing a carbonyl nanolayer or silver nanoparticles coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine containing an amino nanolayer.
[0014] As a further technical solution of the present invention, the specific operation of step S4 is: centrifuging with a high-speed centrifuge at a rotation speed of 15000 rpm to separate the liquid and nanoparticles in the dispersion, removing the supernatant, ultrasonically cleaning the precipitated nanoparticles with deionized water, and then collecting the nanoparticles again with a high-speed centrifuge, repeating 3 times, and then drying with a freeze dryer.
[0015] The third object of the present invention is to provide a new type of lithium metal negative electrode material for use in lithium metal solid-state batteries and lithium metal liquid batteries.
[0016] Compared with the prior art, the present invention has the following advantages and beneficial effects: The lithium-philic particles are lithium-philic. When the current density is less than the limiting current density, the lithium ion concentration on the surface of the lithium-philic particles is evenly distributed. When the lithium ions obtain electrons on the surface of the lithium-philic particles and become lithium, they can nucleate and grow evenly on the surface of the lithium-philic material. The coated nanolayer can be attached to the surface of the lithium-philic particles. The coated nanolayer has polar functional groups. When the current density is greater than the limiting current density, a uniform electric field can be formed on the surface of the lithium-philic particles to induce uniform precipitation of lithium ions. Therefore, under high current density, the growth of lithium dendrites can still be inhibited, thereby increasing the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings: Figure 1 The Li-Li symmetric battery of the present invention is 1 mA / cm 2 The current density and 1 mAh / cm 2 The voltage diagram of the 20th cycle under the surface capacity condition; Figure 2 AgLi 10 -AgLi 10 Symmetrical cell at 1mA / cm 2 The current density is 1 mAh / cm 2 The voltage diagram of the 20th cycle under the surface capacity condition; Figure 3 AgLi 10 @GA-PEI-CG-AgLi 10 @GA-PEI-CG symmetric cell at 1mA / cm 2 The current density is 1 mAh / cm 2 The voltage diagram of the 20th cycle under the surface capacity condition; Figure 4 AgLi of the present invention 10 @GA-PEI-AM-AgLi 10 @GA-PEI-AM symmetrical cell at 1mA / cm 2 The current density and 1 mAh / cm 2 The voltage diagram of the 20th cycle under the surface capacity condition; Figure 5 The Li-Li symmetrical battery of the present invention is 5 mA / cm 2 The current density is 5 mAh / cm 2The voltage diagram of the 20th cycle under the surface capacity condition; Figure 6 AgLi of the present invention 10 -AgLi 10 Symmetrical cell at 5 mA / cm 2 The current density is 5 mAh / cm 2 The voltage diagram of the 20th cycle under the surface capacity condition; Figure 7 AgLi of the present invention 10 @GA-PEI-CG-AgLi 10 @GA-PEI-CG symmetrical cell at 5mA / cm 2 The current density is 5 mAh / cm 2 The voltage diagram of the 20th cycle under the surface capacity condition; Figure 8 AgLi of the present invention 10 @GA-PEI-AM-AgLi 10 @GA-PEI-AM symmetrical cell at 5mA / cm 2 The current density is 5 mAh / cm 2 The voltage diagram of the 20th cycle under the surface capacity condition; Fig. 9 The specific capacity-voltage diagram of Li|LFP at 0.5C rate for 100 cycles of charge and discharge; Fig.10 For AgLi 10 | Specific capacity-voltage diagram of LFP charge and discharge for 100 cycles at 0.5 C rate; Fig.11 For AgLi 10 @GA-PEI-CG|LFP specific capacity-voltage diagram of charge and discharge for 100 cycles at 0.5 C rate; Fig.12 For AgLi 10 @GA-PEI-AM|LFP specific capacity-voltage diagram of charge and discharge for 100 cycles at 0.5 C rate; Fig.13 AgLi of the present invention 10 Surface morphology of @GA-PEI-CG; Fig.14 AgLi of the present invention 10 Surface morphology of @GA-PEI-AM; Fig.15 The present invention is AgLi after lithium plating 10 Surface morphology of @GA-PEI-CG; Fig.16 The present invention is AgLi after lithium plating10 Surface morphology of @GA-PEI-AM. DETAILED DESCRIPTION
[0018] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0019] In the prior art, lithium metal is doped with lithium-philic materials such as silver and magnesium to induce the electrochemical precipitation of lithium ions and inhibit the growth of lithium dendrites. However, this can only be achieved under the condition that the current density is less than the limiting current density. When the current density is greater than the limiting current density, the concentration of lithium ions on the surface of the lithium-philic material is uneven. The lithium nucleation grows faster where the lithium ion concentration is high on the surface of the lithium-philic material, and the lithium nucleation grows slower where the lithium ion concentration is low, thereby forming an uneven plane on the surface of the lithium-philic material, and forming lithium dendrites again.
[0020] Example 1 provides a method for preparing a novel negative electrode material for a lithium battery, comprising the following steps: S1, 5 mg of silver nanoparticles were added to 1 mL of deionized (RO) water and treated at 100 W ultrasonic power for 10 min to make the silver nanoparticles completely and evenly dispersed to obtain a silver nanoparticle dispersion; S2, weigh 50 mg of 3,4,5-trihydroxybenzoic acid, dissolve it in 10 mL of tris (hydroxymethyl)aminomethane (Tris) buffer solution with a pH value of 8.5, and ultrasonicate for 300 s to make the solute dispersed and dissolved evenly, and prepare a Tris solution containing 3,4,5-trihydroxybenzoic acid with a concentration of 5 mg / mL; Weigh 5 mg of polyethyleneimine (PEI, molecular weight 500 Da), dissolve it in 10 mL of pH=8.5 Tris buffer solution, stir until completely dissolved, and prepare a polyethyleneimine solution with a concentration of 0.5 mg / mL; the mass ratio of polyethyleneimine to 3,4,5-trihydroxybenzoic acid is 1:10; S3, slowly adding the two solutions obtained in step 2 to the silver nanoparticle dispersion obtained in step S1 at room temperature, and letting it stand for 0.5 min to allow 3,4,5-trihydroxybenzoic acid and polyethyleneimine to fully polymerize on the surface of the silver nanoparticles, to obtain a dispersion of silver nanoparticles having a carbonyl-containing nanolayer coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine, wherein the coating layer has a thickness of 0.001 μm; S4, the dispersion of silver nanoparticles coated with nanolayers of 3,4,5-trihydroxybenzoic acid and polyethyleneimine obtained in step S3 is separated from the liquid and nanoparticles by a high-speed centrifuge at a speed of 15,000 rpm, the supernatant is removed, the precipitated nanoparticles are ultrasonically cleaned with RO water, and the nanoparticles are collected again by a high-speed centrifuge, and the process is repeated 3 times. The collected nanoparticles are dried in a freeze dryer to obtain silver nanoparticles containing carbonyl nanolayers coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine (abbreviated as Ag@GA-PEI-CG).
[0021] Then, the prepared negative electrode material is used to make a negative electrode sheet, which includes the following steps: (1) Dissolve 50 mg of polyvinylidene fluoride (PVDF) powder in 2 ml of N-methylpyrrolidone (NMP) solution to obtain a 25 mg / ml NMP mixed solution containing PVDF; (2) 0.5 mg of super-p conductive agent was mixed with 4 mg of prepared Ag@GA-PEI-CG negative electrode material, stirred and ground evenly to obtain 4.5 mg of a uniform mixture, wherein the mass ratio of Ag@GA-PEI-CG negative electrode material to super-p conductive agent was 8:1; (3) adding the uniform mixture in step (2) to the mixed solution obtained in step (1), stirring evenly to obtain a uniform slurry; (4) applying the uniform slurry obtained in step (3) uniformly onto the copper foil, drying it at 60° C. for 12 h, volatilizing it, and then drying it at 60° C. under vacuum for 24 h to form a thin film on the copper foil; (5) Cut the film obtained in step (4) into the shape of a pole piece, so that the silver surface loading is 2 mg / cm 2 The pole piece, Fig.13 For AgLi 10 @GA-PEI-CG surface morphology, we can see that the particle size is uniform. Then it is assembled with lithium sheet into a half-cell and electrochemically plated with lithium to obtain a lithium surface loading of 20 mg / cm 2 A new type of AgLi 10 @GA-PEI-CG composites, such as Fig.15 As shown, lithium completely passed through GA-PEI-CG and entered the interior of the silver nanoparticles, the particle size became larger, and remained intact without the formation of lithium dendrites.
[0022] Example 2 provides a method for preparing a novel negative electrode material for a lithium battery, comprising the following steps: S1, 5 mg of silver nanoparticles were added to 1 mL of RO water and treated at 100 W ultrasonic power for 10 min to make the silver nanoparticles completely and evenly dispersed to obtain a silver nanoparticle dispersion; S2, weigh 5 mg of 3,4,5-trihydroxybenzoic acid, dissolve it in 10 mL of pH=8.5 tris(hydroxymethyl)aminomethane (Tris) buffer solution, and ultrasonicate for 300 s to make the solute dispersed and dissolved evenly, and prepare a solution containing 3,4,5-trihydroxybenzoic acid at a concentration of 0.5 mg / mL; Weigh 50 mg of polyethyleneimine (PEI, molecular weight 500 Da), dissolve it in 10 mL of pH=8.5 Tris buffer solution, stir until completely dissolved, and prepare a polyethyleneimine solution with a concentration of 5 mg / mL; the mass ratio of polyethyleneimine to 3,4,5-trihydroxybenzoic acid is 10:1; S3, slowly adding the two solutions obtained in step S2 to the silver nanoparticle dispersion obtained in step S1 at room temperature, and letting it stand for 0.5 min to allow 3,4,5-trihydroxybenzoic acid and polyethyleneimine to fully polymerize on the surface of the silver nanoparticles, to obtain a dispersion of silver nanoparticles having a nanolayer containing amino groups coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine, wherein the thickness of the coating layer is 0.001 μm; S4, the dispersion of silver nanoparticles with a nanolayer coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine obtained in step S3 is separated from the liquid and nanoparticles by a high-speed centrifuge at a speed of 15,000 rpm, the supernatant is removed, the precipitated nanoparticles are ultrasonically cleaned with RO water, and the nanoparticles are collected again by a high-speed centrifuge, and the process is repeated 3 times. The collected nanoparticles are dried in a freeze dryer to obtain silver nanoparticles containing amino groups with a nanolayer coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine (abbreviated as Ag@GA-PEI-AM).
[0023] Then, the prepared negative electrode material is used to make a negative electrode sheet, and the steps are the same as those in Example 1. Fig.14 For AgLi 10 @GA-PEI-AM surface morphology, it can also be seen that the particle size is uniform, and then assembled with lithium sheets into a half-cell, and electrochemical lithium plating is performed to obtain a lithium surface loading of 20 mg / cm 2 A new type of AgLi 10 @GA-PEI-AM composites, such as Fig.16 As shown, lithium completely passed through GA-PEI-AM and entered the interior of the silver nanoparticles, the particle size became larger, and remained intact without the formation of lithium dendrites.
[0024] Example 3 provides a method for preparing a novel negative electrode material for a lithium battery, comprising the following steps: S1, adding 5 mg of silver nanoparticles into 1 mL of RO water, and treating at 100 W ultrasonic power for 10 min to make the silver nanoparticles completely and evenly dispersed to obtain a silver nanoparticle dispersion; S2, weigh 50 mg of 3,4,5-trihydroxybenzoic acid, dissolve it in 10 mL of Tris buffer solution with a pH value of 8.5, and sonicate for 300 s to make the solute dispersed and dissolved evenly, to prepare a Tris solution containing 3,4,5-trihydroxybenzoic acid with a concentration of 5 mg / mL; Weigh 5 mg of polyethyleneimine (PEI, molecular weight 500 Da), dissolve it in 10 mL of pH=8.5 Tris buffer solution, stir until completely dissolved, and prepare a polyethyleneimine solution with a concentration of 0.5 mg / mL; the mass ratio of polyethyleneimine to 3,4,5-trihydroxybenzoic acid is 1:10; S3, slowly adding the two solutions obtained in step 2 to the silver nanoparticle dispersion obtained in step S1 at room temperature, and standing for 5 minutes to allow 3,4,5-trihydroxybenzoic acid and polyethyleneimine to fully polymerize on the surface of the silver nanoparticles, to obtain a dispersion of silver nanoparticles having a carbonyl-containing nanolayer coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine, wherein the coating layer has a thickness of 0.1 μm; S4, the dispersion of silver nanoparticles coated with nanolayers of 3,4,5-trihydroxybenzoic acid and polyethyleneimine obtained in step S3 is separated from the liquid and nanoparticles by a high-speed centrifuge at a speed of 15,000 rpm, the supernatant is removed, the precipitated nanoparticles are ultrasonically cleaned with RO water, and the nanoparticles are collected again by a high-speed centrifuge, and the process is repeated 3 times. The collected nanoparticles are dried in a freeze dryer to obtain silver nanoparticles containing carbonyl nanolayers coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine (abbreviated as Ag@GA-PEI-CG).
[0025] The prepared negative electrode material is then used to make a negative electrode sheet, the steps are the same as in Example 1, and then assembled with a lithium sheet into a half-cell, and electrochemical lithium plating is performed to obtain a lithium surface loading of 20 mg / cm 2 A new type of AgLi 10 Composite material of @GA-PEI-AM.
[0026] Example 4 provides a method for preparing a novel negative electrode material for a lithium battery, comprising the following steps: S1, 5 mg of silver nanoparticles were added to 1 mL of RO water and treated at 100 W ultrasonic power for 10 min to make the silver nanoparticles completely and evenly dispersed to obtain a silver nanoparticle dispersion; S2, weigh 5 mg of 3,4,5-trihydroxybenzoic acid, dissolve it in 10 mL of pH=8.5 tris(hydroxymethyl)aminomethane (Tris) buffer solution, and ultrasonicate for 300 s to make the solute dispersed and dissolved evenly, and prepare a solution containing 3,4,5-trihydroxybenzoic acid at a concentration of 0.5 mg / mL; Weigh 50 mg of polyethyleneimine (PEI, molecular weight 500 Da), dissolve it in 10 mL of pH=8.5 Tris buffer solution, stir until completely dissolved, and prepare a polyethyleneimine solution with a concentration of 5 mg / mL; the mass ratio of polyethyleneimine to 3,4,5-trihydroxybenzoic acid is 10:1; S3, slowly adding the two solutions obtained in step S2 to the silver nanoparticle dispersion obtained in step S1 at room temperature, and standing for 5 minutes to allow 3,4,5-trihydroxybenzoic acid and polyethyleneimine to fully polymerize on the surface of the silver nanoparticles, to obtain a dispersion of silver nanoparticles having a nanolayer containing amino groups coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine, wherein the thickness of the coating layer is 0.1 μm; S4, the dispersion of silver nanoparticles with a nanolayer coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine obtained in step S3 is separated from the liquid and nanoparticles by a high-speed centrifuge at a speed of 15,000 rpm, the supernatant is removed, the precipitated nanoparticles are ultrasonically cleaned with RO water, and the nanoparticles are collected again by a high-speed centrifuge, and the process is repeated 3 times. The collected nanoparticles are dried in a freeze dryer to obtain silver nanoparticles containing amino groups with a nanolayer coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine (abbreviated as Ag@GA-PEI-AM).
[0027] The prepared negative electrode material is then used to make a negative electrode sheet, the steps are the same as in Example 1, and then assembled with a lithium sheet into a half-cell, and electrochemical lithium plating is performed to obtain a lithium surface loading of 20 mg / cm 2 A new type of AgLi 10 Composite material of @GA-PEI-AM.
[0028] Example 5 provides a method for preparing a new type of negative electrode material for a lithium battery, which has the same steps as Example 1, except that the standing time in step S3 is 30 minutes, and the thickness of the final coating layer is 0.5 μm. The prepared negative electrode material is then used to make a negative electrode sheet, and the steps are the same as Example 1. The negative electrode sheet is then assembled with a lithium sheet into a half-cell, and electrochemical lithium plating is performed to obtain a lithium surface loading of 20 mg / cm2 A new type of AgLi 10 @GA-PEI-CG composite material.
[0029] Example 6 provides a method for preparing a novel negative electrode material for a lithium battery, which has the same steps as Example 2, except that the standing time in step S3 is 30 minutes, and the thickness of the final coating layer is 0.5 μm. The prepared negative electrode material is then used to make a negative electrode sheet, and the steps are the same as those in Example 1. The negative electrode sheet is then assembled with a lithium sheet into a half-cell, and electrochemical lithium plating is performed to obtain a lithium surface loading of 20 mg / cm 2 A new type of AgLi 10 Composite material of @GA-PEI-AM.
[0030] Comparative Example 1: In this comparative example, a Li-Li symmetrical battery is selected, and silver nanoparticles, 3,4,5-trihydroxybenzoic acid (GA), and polyethyleneimine (PEI) are not added as negative electrode materials, and the negative electrode plate is a lithium plate.
[0031] Comparative Example 2: AgLi was selected for this comparative example. 10 -AgLi 10 Symmetrical battery, without adding 3,4,5-trihydroxybenzoic acid (GA) and polyethyleneimine (PEI) as negative electrode materials, the negative electrode plate is lithium-silver alloy.
[0032] The following are the relevant performance test data of Example 1, Example 2, Comparative Example 1 and Comparative Example 2.
[0033] Figure 1 The Li-Li symmetric battery in Comparative Example 1 is at 1 mA / cm 2 The current density and 1 mAh / cm 2 Voltage diagram of the 20th cycle under the surface capacity condition.
[0034] Figure 2 For the AgLi in Comparative Example 2 10 -AgLi 10 Symmetrical cell at 1mA / cm 2 The current density and 1 mAh / cm 2 Voltage diagram of the 20th cycle under the surface capacity condition.
[0035] Figure 3 For AgLi 10 @GA-PEI-CG-AgLi 10 @GA-PEI-CG symmetric cell at 1mA / cm 2 Voltage diagram of the 20th cycle under the conditions of current density and surface capacity of 1 mAh cm-2.
[0036] Figure 4For AgLi 10 @GA-PEI-AM-AgLi 10 @GA-PEI-AM symmetrical cell at 1mA / cm 2 The current density and 1 mAh / cm 2 Voltage diagram of the 20th cycle under the surface capacity condition.
[0037] from Figure 1 and Figure 2 By comparison, we can see that the polarization voltage of Li-Li symmetric battery is about 0.36V, while that of AgLi 10 -AgLi 10 The polarization voltage of the symmetrical battery is only about 0.1V, but the voltage fluctuates. This is mainly because silver increases the surface energy of lithium, reduces the nucleation and crystallization energy barriers after lithium ions gain electrons, and improves the kinetic performance of lithium's electrochemical reaction. However, the voltage fluctuates, which is mainly because AgLi 10 The composition and phase distribution of the solid electrolyte interface film (SEI film) on the surface are uneven, resulting in AgLi 10 The electric field distribution on the surface is not uniform, which causes voltage fluctuations.
[0038] like Figure 3 and Figure 4 As shown, AgLi 10 @GA-PEI-CG-AgLi 10 @GA-PEI-CG symmetrical battery voltage is only 0.1V, the voltage is stable. AgLi 10 @GA-PEI-AM-AgLi 10 @GA-PEI-AM symmetric battery polarization voltage is only about 0.1V, and the voltage is stable. This is mainly because the carbonyl polar functional groups uniformly distributed in GA-PEI-CG are AgLi 10 The surface provides a uniform electric field, thus stabilizing the charge and discharge voltage. In addition, the uniformly distributed amino polar functional groups of GA-PEI-AM can also provide AgLi 10 The surface provides a uniform electric field, which stabilizes the charge and discharge voltage.
[0039] Figure 5 The Li-Li symmetric battery in Comparative Example 1 is at 5 mA / cm 2 The current density and 5 mAh / cm 2 Voltage diagram of the 20th cycle under the surface capacity condition.
[0040] Figure 6 For the AgLi in Comparative Example 2 10 -AgLi 10 Symmetrical cell at 5 mA / cm 2 The current density and 5 mAh / cm2 Voltage diagram of the 20th cycle under the surface capacity condition.
[0041] Figure 7 For AgLi 10 @GA-PEI-CG-AgLi 10 @GA-PEI-CG symmetrical cell at 5mA / cm 2 The current density and 5 mAh / cm 2 Voltage diagram of the 20th cycle under the surface capacity condition.
[0042] Figure 8 For AgLi 10 @GA-PEI-AM-AgLi 10 @GA-PEI-AM symmetrical cell at 5mA / cm 2 The current density and 5 mAh / cm 2 Voltage diagram of the 20th cycle under the surface capacity condition.
[0043] By comparison, the Li-Li symmetric battery has a 2 The current density and 5 mAh / cm 2 The polarization voltage under the surface capacity condition increases sharply to about 0.7V, AgLi 10 -AgLi 10 The symmetrical battery increases to about 0.45V. This is mainly because the lithium ion concentration gradient increases after the current density increases, causing lithium and AgLi 10 The uneven lithium ion concentration on the surface leads to the growth of lithium dendrites.
[0044] And AgLi 10 @GA-PEI-CG and AgLi 10 The polarization voltage of @GA-PEI-AM is still only about 0.12 V, which is mainly due to the carbonyl polar functional groups on the surface of GA-PEI-CG and the amino polar functional groups on the surface of GA-PEI-AM. 10 and form a uniform electric field that can make AgLi 10 The lithium ion concentration on the surface is uniform, and the carbonyl polar functional groups of GA-PEI-CG and the amino polar functional groups of GA-PEI-AM can uniformly adsorb lithium atoms to form a uniform precipitation.
[0045] Then, lithium iron phosphate (LFP) was used as the positive electrode to react with Li and AgLi 10 And the negative electrode material prepared in Example 1 forms a full battery, such as Figure 9-12 As shown, after comparison, Fig. 9The specific capacity-voltage diagram of Li|LFP at 0.5 C rate for 100 cycles of charge and discharge shows that the discharge specific capacity is 79 mAh / g and the polarization voltage is 0.78 V. Fig.10 For AgLi 10 |The specific capacity-voltage diagram of LFP charge and discharge for 100 cycles at 0.5C rate shows that the discharge specific capacity is 91 mAh / g and the polarization voltage is 0.6V. Fig.11 For AgLi 10 @GA-PEI-CG|LFP shows a specific capacity-voltage diagram of 100 cycles of charge and discharge at a rate of 0.5 C. It can be seen that the discharge specific capacity is 116 mAh / g and the polarization voltage is 0.29 V. Fig.12 For AgLi 10 @GA-PEI-AM|LFP is shown in the specific capacity-voltage diagram of 100 cycles of charge and discharge at a rate of 0.5 C. It can be seen that the discharge specific capacity is 118 mAh / g and the polarization voltage is 0.28 V. It can be seen that AgLi 10 @GA-PEI-CG|LFP and AgLi 10 @GA-PEI-AM|LFP has a higher specific capacity than Li|LFP and AgLi after 100 cycles. 10 |LFP, which shows that the coating layer with polar functional groups can improve the electrochemical performance of the electrode.
[0046] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A new type of negative electrode material for lithium batteries, characterized in that: The invention comprises lithium-philic particles and a coating nano-layer coated on the outer surface of the lithium-philic particles, wherein the coating nano-layer contains polar functional groups; the lithium-philic particles are silver nano-particles, and the coating nano-layer is a polymer of 3,4,5-trihydroxybenzoic acid and polyethyleneimine.
2. The novel lithium battery negative electrode material according to claim 1, characterized in that: The thickness of the coated nano layer is 0.001-0.5 μm.
3. The novel lithium battery negative electrode material according to claim 1, characterized in that: The mass ratio of the polymer of 3,4,5-trihydroxybenzoic acid and polyethyleneimine is 10:1 or 1:
10.
4. A method for preparing a novel negative electrode material for a lithium battery, used for preparing the novel negative electrode material for a lithium battery according to any one of claims 1 to 3, characterized in that: The steps include: S1, adding silver nanoparticles into deionized water to obtain a silver nanoparticle dispersion; S2, dissolving 3,4,5-trihydroxybenzoic acid in a tris(hydroxymethyl)aminomethane buffer solution to prepare a tris(hydroxymethyl)aminomethane solution containing 3,4,5-trihydroxybenzoic acid; dissolving polyethyleneimine in another tris(hydroxymethylaminomethane) buffer solution to prepare a tris(hydroxymethylaminomethane) solution containing polyethyleneimine; S3, under room temperature, adding the two solutions obtained in step S2 to the dispersion in step S1, and letting it stand for a period of time to obtain a dispersion of silver nanoparticles coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine nanolayers; S4, centrifuging the dispersion obtained in step 3, separating the precipitate, drying and collecting the nanoparticles, and finally obtaining the desired negative electrode material.
5. The method for preparing the novel negative electrode material for lithium battery according to claim 4, characterized in that: The treatment process of step S1 is: treating at 100W ultrasonic power for 10 minutes, and the silver nanoparticles are evenly dispersed to form a dispersion.
6. The method for preparing the novel negative electrode material for lithium battery according to claim 4, characterized in that: The standing time in step S3 is 0.5-30 min.
7. The method for preparing the novel negative electrode material for lithium battery according to claim 4, characterized in that: The negative electrode material finally obtained in step S4 is silver nanoparticles coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine containing carbonyl nanolayers or silver nanoparticles coated with 3,4,5-trihydroxybenzoic acid and polyethyleneimine containing amino nanolayers.
8. The method for preparing the novel negative electrode material for lithium battery according to claim 4, characterized in that: The specific operation of step S4 is: centrifuging with a high-speed centrifuge at a rotation speed of 15000 rpm to separate the liquid and nanoparticles in the dispersion, removing the supernatant, ultrasonically cleaning the precipitated nanoparticles with deionized water, and then collecting the nanoparticles again with a high-speed centrifuge, repeating 3 times, and then drying with a freeze dryer.
9. Use of the novel lithium battery negative electrode material according to any one of claims 1 to 3 or the novel lithium battery negative electrode material prepared by the preparation method according to any one of claims 4 to 8 in solid-state batteries and liquid batteries.
Citation Information
Patent Citations
Composite lithium battery with high cycling stability and large capacity and preparation method thereof
CN103560264A
Lithium anode for high-specific-energy secondary battery
CN106025230A
Lithium-free negative pole piece as well as preparation method and application thereof
CN116190559A
Negative electrode material for lithium metal battery, preparation method and application
CN116779870A
Lithium metal negative electrode, preparation method thereof and lithium metal battery
CN117038847A